2014
DOI: 10.1002/ajmg.a.36535
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygous microdeletion of chromosome 15q13.3 region in a child with hypotonia, impaired vision, and global developmental delay

Abstract: Homozygous or compound heterozygous microdeletion of 15q13.3 region is a rare but clinically recognizable syndrome manifested by profound intellectual disability, muscular hypotonia, intractable seizures, and visual impairment. We identified a compound heterozygous 15q13.3 microdeletion in a 23-month-old girl with global developmental delay, generalized muscular hypotonia, and visual dysfunction. The larger deletion was approximately 1.28 Mb in size and contained seven genes including the TRPM1 and CHRNA7, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…also observed that reported cases carrying a minimal microdeletion in the region encompassing the single CHRNA7 gene,14,15 also included an intergenic region containing regulatory elements potentially accounting for OTUD7A expression. This suggests that the phenotypes observed in patients carrying CHRNA7 deletions may not have resulted from CHRNA7 dysfunction, but instead from an aberrant OTUD7A expression and downstream activity of the encoded deubiquitinase.…”
mentioning
confidence: 75%
“…also observed that reported cases carrying a minimal microdeletion in the region encompassing the single CHRNA7 gene,14,15 also included an intergenic region containing regulatory elements potentially accounting for OTUD7A expression. This suggests that the phenotypes observed in patients carrying CHRNA7 deletions may not have resulted from CHRNA7 dysfunction, but instead from an aberrant OTUD7A expression and downstream activity of the encoded deubiquitinase.…”
mentioning
confidence: 75%
“…Three additional cases with 15q13.3 homozygous deletions reported in 2014 provide some support for the likelihood that biallelic loss of TRPM1 may be associated with characteristic retinal dysfunction. 20,27 However, cases with deletions showing biallelic loss of only CHRNA7 also have visual impairment, thus limiting definitive conclusions. 20,27 With respect to placenta previa, there are studies of embryo implantation in a null mouse model implicating the 15q13.3 region gene KLF13, as well as KLF9, a related gene located at 9q13.…”
Section: Potential Genotype-phenotype Correlationsmentioning
confidence: 99%
“…20,27 However, cases with deletions showing biallelic loss of only CHRNA7 also have visual impairment, thus limiting definitive conclusions. 20,27 With respect to placenta previa, there are studies of embryo implantation in a null mouse model implicating the 15q13.3 region gene KLF13, as well as KLF9, a related gene located at 9q13. 35 These genes encode members of the Krüppel-like family of transcription factors, which are needed to maintain the proper progesterone sensitivity regulation that is essential for successful embryo implantation.…”
Section: Potential Genotype-phenotype Correlationsmentioning
confidence: 99%
“…It has been reported in a total of 11 cases in the literature [9,18,20,28,52,5456]. Three (27.3%) of the 11 published cases are compound heterozygotes [9,56], one with BP4-BP5 and BP3-BP5 deletions, and two BP4-BP5 and D-CHRNA7-LCR-BP5 deletions.…”
Section: Phenotypes Associated With Changes In Chrna7 Copy Numbermentioning
confidence: 99%
“…It has been reported in a total of 11 cases in the literature [9,18,20,28,52,5456]. Three (27.3%) of the 11 published cases are compound heterozygotes [9,56], one with BP4-BP5 and BP3-BP5 deletions, and two BP4-BP5 and D-CHRNA7-LCR-BP5 deletions. Of the other eight (72.7%%) patients, two are homozygous for D-CHRNA7-LCR-BP5 deletions [52,54], and six are homozygous for BP4-BP5 deletions [18,20,28,55] (Figures 2 & 3).…”
Section: Phenotypes Associated With Changes In Chrna7 Copy Numbermentioning
confidence: 99%